APLIKASI PUPUK ORGANIK CAIR (LIMBAH CAIR TAHU) DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT DI PRE-NURSE - Bobby Handoko; Titin Setyorini; Dian Pratama Putra (Program Studi Agroteknologi INSTIPER, 2019)
Fertilization in oil palm nurseries is a required activity to support plant growth. The use of organic fertilizers can be an alternative to reduce the operational costs on oil palm nurseries. This study aims to determine the ef ect of the application of liquid organic fertilizer (tofu liquid waste) and cow manure on the growth of oil palm seedlings in the pre-nursery. The research was conducted at the Educational and Research Garden (KP2) of the STIPER Yogyakarta Agricultural Institute, which is in Maguwoharjo, Depok, Sleman, Yogyakarta. Completely Randomized Design (CRD) consisting of two factors was used as experimental method in this research. The first factor was the concentration of liquid organic fertilizer (tofu liquid waste) which consists of 4 levels: 0%, 25%, 50%, 75%. The second factor was the dose of cow manure consisting of 4 levels: 0 g, 100 g, 200 g, 300 g. The results were analyzed by Analysis of Variance and Duncan’s Multiple Range Test, both with significance level of 5%, to find out the dif erences among treatments. The results showed that there was no significant interaction between the treatment of tofu liquid waste concentration and the dose of cow manure on all observed parameters. However, there was still a tendency that the concentration of tofu liquid waste 50% and the dose of cow manure 100 g was the best combination in all parameters. Keywords: Tofu liquid waste, cow manure, oil palm seedling